EFEK BIOLARVASIDA NYAMUK Aedes aegypti DARI GRANUL EKSTRAK DAUN JERUK NIPIS (Citrus aurantifolia) - Yunita Mangampa; Michrun Nisa; Nurul Fahimah; Sriwanti Lisu Rannu; Muh Anugrawan; Febi Rofina Doa (Jurnal Ilmiah Manuntung, 2017)
Dengue Haemorrhagic Fever (DHF) is still one of the problems in Indonesia. Natural materials that has the property of killing the mosquito vector one of them is a lime leaf. lime leaf extract contains limonoids compounds that serve as larvacide.Tujuan of this research is to make granule extract lime leaf (Citrus aurantifolia) which has the ability as a mosquito killer biolarvacide. This type of research is a laboratory experiment. The population in this study were all three instars of Aedes aegypti larvae aged 3-4 days. The results showed that there was granule effect of lime leaf extract (Citrus aurantifolia) to the death of Aedes aegypti mosquito larvae. The granule concentration of lime leaf extract (Citrus aurantifolia) which is effective in killing Aedes aegypti mosquito larvae is 15% extract concentration formulated in granule form with percent mortality of 76.7% larvae.